Microfluidic devices fabrication for bioelectrokinetic system applications - Md. Yunus, Nurul Amziah (InTech, 2013)
The research and development of microfluidic technologies has increased tremendously over the past twenty years. The technology allows designers to create small, portable, robust, low cost and easy-to-use diagnostic instruments that offer high levels of capability and versatility. Microfluidic systems will decrease reagent consumption and reduce cost per analysis. It also reduces analysis time and provides better controllable process parameters in chemical reactions.